DEVELOPING PUPILS’ DIVERGENT THINKING THROUGH COGNITIVE TASKS - Suyarov Kusharbay Tashbayevich (Bright Mind Publishing, 2025)
This article explores the didactic potential of using cognitive tasks to develop students’ divergent thinking through solving physics problems by multiple methods. Divergent thinking is understood as the ability to generate several alternative solutions, ideas, or approaches to a given problem, which is a key component of creativity and scientific reasoning. The study is based on the analysis of typical physics problems solved using traditional (convergent) and alternative (divergent) solution strategies. Two representative physics problems were selected and solved using several methods, including analytical, graphical, kinematic, and average-value approaches. Each solution method was analyzed in terms of the type of thinking it predominantly develops.
Keywords: Divergent thinking, convergent thinking, cognitive tasks, physics problem solving, creativity, multiple-solution tasks, scientific thinking.